RADIO ULNAR SYNOSTOSIS: A CASE REPORT - Avadhani, Ramakrishna; S., Bindhu; Vikram; U., Dhanesh Kumar K.; Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2011)
Congenital radio-ulnar synostosis is caused by a failure of segmentation between the radius and ulna. It occurs rarely, with approximately 350 cases reported. Congenital radioulnar synostosis is equally affected in males and females with half of patients showing bilateral involvement. While most cases of congenital radio-ulnar synostosis occur spontaneously around one in five cases is associated with a family history of the same affliction. This condition can also occur as part of an underlying syndrome or in association with other developmental abnormalities. Congenital radio ulnar synostosis is diagnosed by clinicians through medical history and careful physical examination. X-rays or CT scans are be used to confirm the deformity. The diagnosis of congenital radio-ulnar synostosis is more often made in late childhood or at adolescence, as pain is rarely a complaint and much mobility of elbow flexion and extension preserved. In relatively mild cases, when patients themselves may notice subtle limitations or differences in forearm rotation the diagnosis is typically made at an earlier age.
Keywords: Synostosis; interosseus membrane; ossification; segmentation